2021
DOI: 10.1016/j.omtn.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-92a-3p regulates osteoblast differentiation in patients with concomitant limb fractures and TBI via IBSP/PI3K-AKT inhibition

Abstract: Patients who sustain concomitant fractures and traumatic brain injury (TBI) are known to have significantly quicker fracture-healing rates than patients with isolated fractures. The mechanisms underlying this phenomenon have yet to be identified. In the present study, we found that the upregulation of microRNA-92a-3p (miRNA-92a-3p) induced by TBI correlated with a decrease in integrin binding sialoprotein (IBSP) expression in callus formation. In vitro, overexpressing miRNA-92a-3p inhibited IBSP expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Activating PI3K/AKT pathway can not only promote the osteogenic differentiation of bone marrow stem cells ( Zhao et al, 2020 ) but also enhance the viability of osteoblasts ( Xie et al, 2020 ). In addition, the activation of the PI3K/AKT pathway is one of the mechanisms that the fracture healing rate of TBI patients is faster than that of single fracture patients ( Hu et al, 2021 ). Chlorogenic acid, the active ingredient of HPASD, has been reported to increase femoral bone mineral density and promote osteogenic differentiation of bone marrow stem cells by activating PI3K/AKT pathway ( Zhou et al, 2016 ), and Puerarin was proved to stimulate the human osteoblast differentiation and prevent osteoporosis by activating the PI3K/AKT ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activating PI3K/AKT pathway can not only promote the osteogenic differentiation of bone marrow stem cells ( Zhao et al, 2020 ) but also enhance the viability of osteoblasts ( Xie et al, 2020 ). In addition, the activation of the PI3K/AKT pathway is one of the mechanisms that the fracture healing rate of TBI patients is faster than that of single fracture patients ( Hu et al, 2021 ). Chlorogenic acid, the active ingredient of HPASD, has been reported to increase femoral bone mineral density and promote osteogenic differentiation of bone marrow stem cells by activating PI3K/AKT pathway ( Zhou et al, 2016 ), and Puerarin was proved to stimulate the human osteoblast differentiation and prevent osteoporosis by activating the PI3K/AKT ( Wang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, poor fracture healing remains a major clinical challenge. Current studies have proved that osteoblasts regulate new bone formation in fracture healing, and differentiate and proliferate under the influence of cytokines, hormones, growth factors, and other factors [ 17 ]. Although previous studies have confirmed that miR-497-5p [ 9 ] and others are involved in the process of fracture healing, miR-223-3p associated with osteoblasts was selected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients combined with fracture and TBI have long been observed to have a obvious short healing period than the isolated fracture patients. And prior studies have reported a potential relationship between TBI and rapid fracture healing [3][4]. However, the potential mechanisms underlying this interesting phenomenon remain unknown.…”
Section: Introductionmentioning
confidence: 99%